A produção do gênero artigo de opinião no 9º ano do ensino fundamental. - Silva , Eduardo Souza da (2020)
This action research, with a qualitative approach and a descriptive-interventionist nature, aimed, based on proposals for reading, interpretation, debate and text production, through a work with the genre opinion article, to develop in the student the ability criticism, through the instrumentalization of this genre, held in a public school in the city of Belém-PB. As proposed by PCN (1998), by BNCC (2017), by Bakhtin (2011) and Marcuschi (2003), working with textual genres in Portuguese Language Classes is essential, due to the context of coexistence of the subjects involved, the students. Based on this, we opted for the opinion article, which is a genre that allows interaction between author and reader, in addition to creating a space for reflection on various issues present in its context, its circulation space. This characteristic gives the student autonomy to discuss, to express opinions and to argue about the most diverse themes. The work was carried out from a didactic sequence, as guided by Dolz, Noverraz, Schneuwly (2004), with reading activities of the genre in question, characterizing it structurally and discursively based on the contributions of Beltrão (1980), Rodrigues (2000) and Vivaldi (1998), their production and context of printed and digital circulation. The results obtained went far beyond technical learning with regard to writing and the development of the students' reflective capacity, as it enabled them to become literate citizens and aware of their daily responsibilities.